2016
DOI: 10.1093/nar/gkw137
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of ribosome drop-off inE. coli

Abstract: Premature ribosome drop-off is one of the major errors in translation of mRNA by ribosomes. However, repeated analyses of Ribo-seq data failed to quantify its strength in E. coli. Relying on a novel highly sensitive data analysis method we show that a significant rate of ribosome drop-off is measurable and can be quantified also when cells are cultured under non-stressing conditions. Moreover, we find that the drop-off rate is highly variable, depending on multiple factors. In particular, under environmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 41 publications
4
85
0
Order By: Relevance
“…Codon elongation rates are usually estimated assuming that the ribosome density at codon i is proportional to the ribosome's dwell time on that particular codon 15,16,[19][20][21][22][23][24] ; this assumption follows from the conservation of the ribosome current assuming no ribosome drop-off. Our estimate of the drop-off rate of ∼ 10 −3 s −1 (obtained from the probability of premature termination estimated to 10 −4 per codon 25,26 and the elongation rate of the order of magnitude of ≈ 10 codon/s) justifies the hypothesis. The inferred elongation rates are then checked against mRNA codon sequence features such as codon usage bias, tRNA availability and mRNA secondary structures.…”
Section: Introductionsupporting
confidence: 74%
“…Codon elongation rates are usually estimated assuming that the ribosome density at codon i is proportional to the ribosome's dwell time on that particular codon 15,16,[19][20][21][22][23][24] ; this assumption follows from the conservation of the ribosome current assuming no ribosome drop-off. Our estimate of the drop-off rate of ∼ 10 −3 s −1 (obtained from the probability of premature termination estimated to 10 −4 per codon 25,26 and the elongation rate of the order of magnitude of ≈ 10 codon/s) justifies the hypothesis. The inferred elongation rates are then checked against mRNA codon sequence features such as codon usage bias, tRNA availability and mRNA secondary structures.…”
Section: Introductionsupporting
confidence: 74%
“…These findings point to a necessary reduction in the number of productively translating ribosomes, due to a variety of possible reasons including ribosome mis-assembly 35 , inactivation 36 , and drop-off 37 as will be discussed below. However direct quantitative characterization of the state of ribosome activity by polysome profiling have yielded inconclusive and conflicting results in the past 38,39 , due to experimental challenges such as the fragility of polysomes or polysome run off which convert a fraction of polysomes to ribosome subunits or 70S monosomes during the sample collection process 10,40 .…”
Section: Results and Analysismentioning
confidence: 89%
“…Recently, it was suggested that the ribosome drop off rate can be predicted based on the analysis of the decrease in ribosome density along coding regions via ribosome profiling data (165). These data can be used in the future when ribosome drop off rates are integrated into translation models.…”
Section: Introductionmentioning
confidence: 99%